The expression and prognostic value of transporter 1, ATP binding cassette subfamily B member in clear cell renal cell cancer with experimental validation - Wang, Zhen-Da; Tian, Xi; Wang, Yue; Wang, Jun-Jie; Ye, Shi-Qi; Huang, Yong-Qiang; Qu, Yuan-Yuan; Chang, Kun; Shi, Guo-Hai; Ye, Ding-Wei; Gu, Cheng-Yuan (Frontiers in Oncology, 2022)
Transporter associated with antigen processing 1(TAP1), is involved in the pumping of degraded cytosolic peptides across the endoplasmic reticulum into the membrane-bound compartment where class I molecules assemble. TAP1 has been found to play an important role in antigen presentation in innate immunity. However, the role of TAP1 in ccRCC remains to be clearified. In this research, We found that TAP1 expression elevated in ccRCC tissues at mRNA and protein levels. And high-TAP1 expression indicated a worse prognosis. Transwell assay and Scratch assay in vitro demonstrated that TAP1 promoted RCC migration and played a significant role in metastasis. More immune cells were infiltrated in cancer tissues when TAP1 expression increased. And TAP1 was related to immune regulator genes. GSEA showed that it mainly participated in immune regulation, especially related to IFN response. We found increasing TAP1 expression suggested a high-level IFN response. Then, we analyzed transcription factors affecting TAP1 expression. IRF1, IRF2, and NF-KB1 bind to the TAP1 promoter. In addition, RNA modification also engaged in its post-transcriptional control. We used the single-cell database CancerSEA to predict RCC biological function. CancerSEA indicated that high-level TAP1 expression is positively associated with EMT and inversely with Cell Cycle. In view of TAP1’s role in immune regulation, we predicted effective drugs based on TAP1 expression. We found that high TAP1 expression is indeed associated with resistance to many drugs, but still identified some drugs that are still effective based on high TAP1 expression. Through the analysis of various databases, we determined the high expression of TAP1 in renal cell carcinoma and suggested a poor prognosis for renal cell carcinoma. TAP1 is closely related to the immune microenvironment. It may eventually affect migration through the immune microenvironment.